Analisis Kualitas Layanan Melalui E-Plavon (Pelayanan Via Online) Di Desa Trosobo, Kecamatan Taman, Kabupaten Sidoarjo - Kurnia, Tessa; Rosdiana, Weni (Universitas Negeri Surabaya, 2023)
Plavon (Online Service) is a service that can be used to request population administration services developed by the Sidoarjo Regency Population and Civil Registration Office. The purpose of this study to describe and analyze the quality of service through E-Plavon (Online Service) Trosobo Village. The research using theory by Zeithaml, et al based on 5 indicators, tangible, reliability, responsiveness, assurance, and empathy. The type of research used is descriptive with a qualitative approach. The results showed that quality of service First, tangible indicators include the appearance of E-Plavon and the appearance of employees have been fulfilled, the service process still constrained by the community not knowing the stages of use, and facilities are constrained by the community not knowing how to minimize files. Second reliability indicator includes the accessibility of E-Plavon and the officer's ability to use tools has een fulfilled. Third indicator of responsiveness includes complaints that are constrained by the suggestion box not being used and fast service has been fulfilled. Fourth, assurance indicators include service times that are often late and service fees are good. Fifth, the empathy indicator, which is non-discriminatory, is constrained because there are no other language options displayed. Suggestions by researchers are to make a service flow chart through E-Plavon in Trosobo Village which is made x banner and uploaded through social media, reactivate the suggestion box at the Trosobo Village Government, increase the number of Sidoarjo Regency Dispendukcapil employees in the E-Plavon operator section, Add other language options to the E-Plavon service.